Procedure For Development Of Lesson Materials For Islamic Religious Education - Nida Alfiah (AIUA Journal of Islamic Education, 2020)
The development of subject matter is closely related to the development of teaching materials. Because the success of teachers, especially PAI teachers in developing subject matter, cannot be separated from their success in making teaching materials. However, in the reality of education in the field, especially Islamic education, there are still many educators who still use conventional teaching materials, namely teaching materials that are left to use so that learning occurs not contextually, less interesting, monotonous, and does not suit the needs of students Therefore, PAI teachers are required to develop their creativity in compiling teaching materials that are innovative, varied, interesting, contextual and in accordance with the level of student needs. To examine these problems, the research used the literature study method. The problems discussed in this paper are first, to explain the meaning of PAI material development, secondly to mention the scope of PAI material development. Third, explain the systematic preparation of PAI material. Fourth, explain the procedure for developing PAI materials through the development of teaching materials.